2014
DOI: 10.1080/09168451.2014.910097
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin glucuronides induce adipocyte differentiation via activation and expression of peroxisome proliferator-activated receptor-γ

Abstract: In previous reports, hesperidin, a flavonoid glucoside from citrus fruit, is hydrolyzed to hesperetin, an aglycone of hesperidin, and converted to the hesperetin glucuronides (H7-OG and H3′-OG) in vivo and depresses blood glucose levels. But there are no reports on the activity of hesperetin glucuronides. To determine the activity of hesperetin glucuronides, H7-OG and H3′-OG were synthesized and peroxisome proliferator-activated receptor-γ (PPARγ) agonist activity was observed at 250 μm. These glucuronides acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Another study showed that eriodictyol had inhibitory effects on mRNA expression of IL-6 and TNF-α (Lee, 2011). Some mechanisms have been proposed to explain the anti-inflammatory properties of citrus flavonoids, which include activation of PPARγ expression and inhibition of nuclear factor kappa B (NFκB), with consequent reduction of inflammatory cytokine secretion and increase of adiponectin (Gamo, Miyachi, Nakamura, & Matsuura, 2014;Lee, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that eriodictyol had inhibitory effects on mRNA expression of IL-6 and TNF-α (Lee, 2011). Some mechanisms have been proposed to explain the anti-inflammatory properties of citrus flavonoids, which include activation of PPARγ expression and inhibition of nuclear factor kappa B (NFκB), with consequent reduction of inflammatory cytokine secretion and increase of adiponectin (Gamo, Miyachi, Nakamura, & Matsuura, 2014;Lee, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the transport mechanisms for phase II conjugates (sulfates and glucuronides) of hesperidin assumes great importance because 1) these hydrophilic conjugates are the main circulating metabolites; and 2) the conjugates possess many types of biologic activities, such as antioxidant and anti-inflammatory effects (Proteggente et al, 2003;Trzeciakiewicz et al, 2010;Yang et al, 2012;Yamamoto et al, 2013;Gamo et al, 2014). It has been shown that multiple transporters (BCRP, MRP2, and MRP3) are potentially responsible for efflux transport of hesperetin glucuronides (Brand et al, 2008(Brand et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Skin, oral cancer prevention PPARγ ligand/activator Apigenin Inhibits cutaneous photocarcingenesis 43 and chemical carcinogenesis 44 PPARγ ligand (EC 50 = 7.9 μM) a 45 Biochanin A Inhibition of DMBA-induced oral cancer b 46 PPARγ ligand 47 PPARγ ligand (EC 50 = 9.6 μM) 45 PPARγ ligand (EC 50 < 1 μM) 48 Caffeic acid Suppresses cutaneous photocarcinogenesis 49 and chemical carcinogenesis 50 Anticancer activity dependent on PPARγ 49 Chrysin Chrysin derivatives suppress cutaneous chemical carcinogenesis 51 PPARγ ligand (EC 50 = 9.8 μM) 45 Daidzein Inhibition of DMBA-induced oral cancer 46 PPARγ ligand (EC 50 = 73 μM) 48 Equol (daidzein metabolite) Suppresses photocarcinogenesis 52 PPARγ ligand (EC 50 = 3.7 μM) 48 Genestein Inhibits chemical carcinogenesis 53 PPARγ ligand (EC 50 = 16.7 μM) 45 PPARγ ligand (K i = 5.7 μM) 48 c Hesperidin Inhibition of chemical carcinogen-induced oral 54 and cutaneous carcinogenesis 55 PPARγ ligand (EC 50 = 6.6 μM) 45 Glucuronide metabolites are also PPARγ ligands with partial agonist activity 56,57 Naringenin Inhibits cutaneous photocarcinogenesis 58 caffeic acid was accompanied by its ability to suppress inflammation and inflammatory mediator release through activation of PPARγ. 49 Similarly, the PPARγ ligands equol 90 and chrysin 91 have been shown to have potent anti-inflammatory activity along with their cancer chemopreventive activity.…”
Section: Phytochemicalmentioning
confidence: 99%